Lung Function Disturbance Based on Student Characteristic in Surabaya Dental Laboratory - Eny Inayati; Sonya Harwasih; Sri Redjeki Indiani (Jurnal Vokasi Indonesia, 2017)
The dental technician program of Airlangga University teaches and trains aspiring dental technicians. During three years of study, students manufacture dental prostheses such as cobalt chromium coping and acrylic dentures and perform other procedures, such as crown and bridge restoration. However, the use of dental prostheses material might cause respiratory diseases, skin problems, and neurotoxicity. Few respiratory diseases have been reported related to the occupation of dental technician, and epidemiology studies have shown high prevalence of pneumoconiosis linked with exposure duration. Lung function disturbance severity in dental laboratories is affected by some factors, such as the characteristics of workers in such a setting. This study aims to investigate the lung function representation of students of the dental technician program of Airlangga University in relation to student characteristics in the dental laboratory. This study is an observational decriptive study. Data are obtained by using a questionnaire and a literature review, and lung physiological examination is conducted using spirometry. Examination data results are presented in the form of a ratio scale and analyzed by using descriptive statistics. Conclusion: No significant difference in lung function was observed between smokers and non-smokers and between mask-wearers and non-mask-wearers.